Advancing gender equality to improve HIV prevention: A study of practice. Issue 4 (16th December 2016) - Mannell, Jenevieve
Abstract : Addressing gender inequality as a social driver of HIV risk and vulnerability has become a key activity of non-governmental organisations (NGOs) in South Africa. This paper sheds light on the environmental factors that influence gender and HIV activities in this context. A multisite ethnographic study including 150 hours of participant observation and 32 in-depth interviews was conducted with 26 NGOs carrying out gender and HIV prevention interventions. Using thematic network analysis, 108 different intervention activities were identified, categorised and further analysed to explore environmental factors that influence the design and delivery of these activities. The findings highlight how practitioners draw on different theories of change about how to address the gender inequalities that contribute to HIV risk and vulnerability, which in turn influence the way interventions are delivered. Despite these theoretical differences, commonalities arise in practitioners' use of popular narratives about the right to health and lived experiences of AIDS to ensure interventions are contextually relevant and to gain buy-in from participants. Other environmental factors influencing intervention activities include the role that insecure funding for gender plays in undermining the capacity of practitioners to design interventions based on their local knowledge and experience by forcing NGOs to adapt to the priorities of international donors.